Pendidikan, Kemampuan Teknik Personal Dan Kecanggihan Teknologi Informasi Terhadap Kinerja SIA Pada LPD Kecamatan Bebandem - Pradnya Dewi, Ni Kadek Irma; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi, 2024)
This study analyzes the influence of education level, personal technical abilities and information technology sophistication on AIS performance in the LPD of Banyakem District. The research population was 15 LPDs, with a sample size of 100 respondents selected using a non-probability method, namely purposive sampling technique. The collected data was analyzed using multiple linear regression analysis techniques. The results of the study prove that the level of education has no effect on AIS performance, personal technical ability has a positive effect on SIA performance, information technology sophistication has a positive effect on AIS performance. Keywords: Education; Personal Engineering Ability; IT sophistication; SIA performance